Resocialisation as an obligation, right and remedy under international and African regional human rights law in the fulfilment of African women's rights - Mahmoudi, Anisa (Stellenbosch : Stellenbosch University, 2023)
Thesis (LLD)--Stellenbosch University, 2023.